JAVA TRADITIONAL DELIVERY RITUAL INSTRUMENTS IN THE WORK OF DODOT BATIK - Danang Priyanto; Sri Hesti Heriwati (LPPMPP Institut Seni Indonesia Padangpanjang, 2022)
This article entitled “Javanese Traditional Birth Ritual Devices in Dodot Batik Works” focuses on the process of creating written batik dodot with the idea of Javanese traditional birth ritual tools. Interest in the existence of these devices is starting to be unknown in the community. The fact that conventional Javanese childbirth is no longer used in the early 21st century in Java is clarified by the Minister of Health Regulation (Permenkes) no. 97 of 2014 states that childbirth must be carried out in a health care facility (Fasyankes) through a midwife who is an expert in the field of obstetrics. The purpose of the creation is to create a handmade batik dodot based on the idea of a traditional Javanese birth ritual device that will be applied to the body with a draping technique. The art used is a symbolic concept with the concept of stacking which emphasizes the creation of the components that make up the batik pattern consisting of the main, supporting, and isen-isen motifs. Analysis of the data used using an interpretation method through an aesthetic approach. The steps of creation include 1) research using ethical and emic data sources, 2) experiments emphasizing dye experiments and central motif sketching techniques, 3) contemplating the stage of finding symbols/metaphors, and 4) forming to make arrangements into a design pattern ( prototype). The works created are four dodot works with a length of 106 cm and a width of 520 cm. The work produced is Anjangkepi Gesang with the philosophy of hope that his parents will be able to fulfill all his needs, Ambuka Science with the philosophy of hope that both parents will be able to understand all knowledge, Angganda Arum with the philosophy of hope that both parents will have a beautiful life and happy, Amadangi Jagad with the philosophy of the hope of both parents that one day his son will be able to benefit the environment around him. The dodot created is applied to the body through a draping technique by forming wrinkles, pleats, and drapes.Keywords: Ritual Devices; Javanese Customary Birth; Dodot; Batik. PIRANTI RITUAL PERSALINAN ADAT JAWA DALAM KARYA DODOT BATIK AbstrakArtikel ini berjudul “Piranti Ritual kelahiran Adat Jawa Dalam Karya Dodot Batik” difokuskan pada proses cipta dodot batik tulis dengan ide piranti ritual kelahiran adat Jawa. Ketertarikan pada keberadaan piranti tersebut yang mulai tidak dikenal di tengah masyarakat. Fakta bahwa praktek persalinan adat Jawa sudah tidak lagi digunakan pada awal abad 21 di Jawa diperjelas dengan Peraturan Menteri Kesehatan (Permenkes) no. 97 tahun 2014 yang tertulis persalinan harus dilakukan di fasilitas pelayanan kesehatan (Fasyankes) dengan melalui bidan yang ahli pada bidang obstetri. Tujuan penciptaan adalah menciptakan karya dodot batik tulis bersumber ide piranti ritual kelahiran adat Jawa yang akan diaplikasikan ke tubuh dengan teknik draping. Konsep seni yang digunakan adalah konsep simbolik dengan konsep tata susun yang menekankan penciptaan komponen motif penyusun pola batik terdiri dari motif utama, pendukung dan isen-isen. Analisis data yang digunakan menggunakan metode interpretasi dengan melalui pendekatan estetika. Langkah-langkah penciptaan meliputi 1) riset dengan memanfaatkan sumber data etik dan emik, 2) eksperimen menekankan pada eksperimen bahan pewarna dan teknik skets motif utama, 3) perenungan tahap menemukan simbol/metafora, dan 4) pembentukan melakukan penyusunan menjadi sebuah pola desain (purwa rupa). Karya yang diciptakan berupa empat buah karya dodot dengan panjang 106 cm dan lebar 520 cm. Karya yang dihasilkan adalah Anjangkepi Gesang dengan filosofi harapan kedua orangtua agar kelak putranya mampu mencukupi segala kebutuhannya, Ambuka Ilmu dengan filosofi harapan kedua orangtua agar kelak putranya mampu dalam memahami segala pengetahuan, Angganda Arum dengan filosofi harapan kedua orangtua agar kelak putranya memiliki kehidupan yang indah dan bahagia, Amadhangi Jagad dengan filosofi harapan kedua orangtua agar kelak putranya mampu bermanfaat bagi lingkungan di sekitarnya. Dodot yang telah diciptakan diaplikasikan pada tubuh melalui teknik draping dengan membentuk kerutan, lipitan dan draperi.Kata kunci: Piranti Ritual; Persalinan Adat Jawa; Dodot; Batik.